(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: There is no unanimously adopted approach to titrating laser parameters in subthreshold retinal laser photocoagulation without ophthalmoscopically visible fundus changes. Purpose: To compare the ultrastructural changes in the rabbit chorioretinal complex after various modes of 577-nm and 532-nm laser photocoagulation. Materials and Methods: Ten rabbits (20 eyes) were involved in the experimental study. Eight (10 eyes) of them underwent different modes of 577-nm or 532-nm laser photocoagulation, and were euthanized at postlaser days 1 (4 rabbits) or 14 (4 rabbits). Ultra-thin sections of their ocular tissue specimens were subjected to electron microscopy and assessed for the state of their choriocapillaries, RPE and photoreceptor cells. In addition, 2 intact rabbits (4 eyes) were used as controls for comparison. Results: 577-nm or 532-nm conventional RLPC resulted in damage to RPE cells, all photoreceptor compartments and choriocapillaries; 577-nm or 532-nm selective RLPC resulted in damage to RPE cells and photoreceptor outer and inner segments, and 577-nm micropulse RLPC with the power setting adjusted to 50% threshold resulted in damage mostly to apical aspects of RPE cells and photoreceptor outer segments. Conclusion: 577-nm micropulse RLPC with the power setting adjusted to 50% threshold is a more photoreceptor- and choriocapillaris-sparing approach compared to 577-nm or 532-nm conventional and selective RLPC, and can be used in clinical practice as a laser treatment approach with the least invasive effect on the chorioretinal complex.